2023
DOI: 10.3390/metabo13080905
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Production of Secondary Metabolites via the Application of Biogenic Zinc Oxide Nanoparticles in the Calli of Delonix elata: A Potential Medicinal Plant

Abstract: The implementation of nanotechnology in the field of plant tissue culture has demonstrated an interesting impact on in vitro plant growth and development. Furthermore, the plant tissue culture accompanying nanoparticles has been showed to be a reliable alternative for the biosynthesis of secondary metabolites. Herein, the effectiveness of zinc oxide nanoparticles (ZnONPs) on the growth of Delonix elata calli, as well as their phytochemical profiles, were investigated. Delonix elata seeds were collected and ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 79 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The current DPS application indicated that the increased expression of CHS, CHI and FLS directly contributed to the upregulation of flavanols (catechin, quercetin and rutin) and flavanones (naringenin). Similarly, the overproduction of quercetin and rutin in Delonix elata callus was recorded by nanoparticles elicitation due to the induction of physiological and biochemical pathways [ 56 ]. However, the addition of the DPS-recommended dose (8 g/l) significantly decreased the kaempferol content relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…The current DPS application indicated that the increased expression of CHS, CHI and FLS directly contributed to the upregulation of flavanols (catechin, quercetin and rutin) and flavanones (naringenin). Similarly, the overproduction of quercetin and rutin in Delonix elata callus was recorded by nanoparticles elicitation due to the induction of physiological and biochemical pathways [ 56 ]. However, the addition of the DPS-recommended dose (8 g/l) significantly decreased the kaempferol content relative to the control.…”
Section: Discussionmentioning
confidence: 99%